High-performance nutrition for masters athletes - Antonucci, Lauren A. 1974- (2021)
"This book provides current, credible nutrition guidance for athletes who are 35 years old or older. The content-which includes charts, meal plans, and expert interviews-applies across all sports, with emphasis on endurance sports"--Provided by publisher.
Ms. Camia (Recommending faculty) AY 2022-2023
Includes bibliographical references (pages 231-243) and index.
Keywords: Athletes -- Nutrition; Cooking